2021
DOI: 10.1177/22925503211019617
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Reverse Sural Flap in Covering Diabetic Foot Ulcers: A Systematic Review and Meta-Analysis

Abstract: Background: The reverse sural fasciocutaneous flap (RSFCF) has been used with success to cover noncomplicated foot and ankle soft tissue defects. However, there are some controversies when it is used in patients having chronic diabetic foot ulcers. This aim of this meta-analysis was to evaluate the efficacy of RSFCF in covering diabetic foot and ankle ulcers. Methods: A systematic review was undertaken from MEDLINE, EMBASE, Web of Science, Cochrane Library, and Google Scholar. Only diabetic foot and ankle ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(211 reference statements)
0
4
0
1
Order By: Relevance
“…It offers abundant, thin tissue with effortless dissection. The donor site morbidity, lack of available vascularized tendon and the relatively high complication rate of 26.4%, especially in the elderly and in patients with venous insufficiency render it a backup solution in our practice [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It offers abundant, thin tissue with effortless dissection. The donor site morbidity, lack of available vascularized tendon and the relatively high complication rate of 26.4%, especially in the elderly and in patients with venous insufficiency render it a backup solution in our practice [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin grafting of the donor site may lead to complications, including infection, depression deformity, medial plantar contracture, and nerve irritation or sensory disturbance of the medial plantar nerve and its branches (Bibbo, 2012; Wan et al, 2011). Similarly, the donor site morbidity for RSF and ALTF, including infection, hematoma, and skin necrosis, is minimal, and these complications can be resolved with simple procedures such as antibiotics, debridement, and primary closure (Yammine et al, 2022). Nerve related complications such as hypoesthesia of the lateral aspect of the foot in RSF and lateral thigh paresthesia in ALTF can occur (Collins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The sural flap is a versatile and effective alternative to microsurgical reconstruction of soft tissue defects in the lower leg. 5,49 Improving the survival of these flaps is critically dependent on the preoperative assessment of distal circulation using advanced diagnostic imaging. 6,10,18 Surgeons should then be prepared to accommodate individual patient risk factors by utilizing evidence-based modifications similar to those discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…48 A recent systematic review and meta-analysis of sural flaps in the coverage of diabetic ulcers reported no significant associations between tunnel width, presence of a tunnel or venous congestion, and total flap loss (p > 0.05). 49 While the literature is limited regarding the effectiveness of tunnels, it may be appropriate to make this decision intraoperatively based on the laxity of the skin, patient comorbidities, and wound qualities. 32…”
Section: Tunnelingmentioning
confidence: 99%